Peningkatan Kreativitas Siswa pada Pembelajaran Teselasi Bangun Datar Melalui Media Keramik - Widowati Widowati; Kartono Kartono; Suryoto Suryoto; Y.D. Sumanto; Ratna Herdiana; Eka Triyana; Slamet Aji Pamungkas (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2025)
Mathematics learning, particularly in geometry, is often perceived as abstract and less engaging by students, leading to reduced interest and creativity. One of the geometry topics that demands a more creative and concrete approach is the tessellation of flat shapes, which emphasizes the understanding of patterns, symmetry, and regularity of shapes. The absence of contextual learning media has contributed to students’ low enthusiasm and limited ability to apply concepts in real-life contexts. This community service activity was designed to address these challenges by enhancing students’ creativity and conceptual understanding through the use of ceramic media as an innovative and enjoyable learning tool. The program was conducted at SD Negeri 1 Rowosari, Tembalang District, Semarang City, involving mathematics teachers, elementary school students, and university students. The implementation method included training and mentoring sessions. Activities encompassed the introduction of tessellation concepts, hands-on demonstrations, and the guided creation of tessellation patterns using ceramic media. Participants consisted of teachers and students who actively engaged in both theoretical and practical sessions. Evaluation was conducted through pre-test and post-test questionnaires administered before and after the training. The results revealed a significant improvement in students’ average scores after the activity. Pre-test data showed that approximately half of the students scored above the average, with two students achieving nearly perfect scores. Post-test results indicated that most students demonstrated increased understanding and creativity in applying tessellation concepts. Nevertheless, a small number of students still required further guidance, particularly in translating abstract tessellation concepts into real-life applications. Overall, the findings suggest that integrating ceramic media into mathematics learning is effective in making abstract geometry concepts more tangible, stimulating students’ creativity, and improving learning outcomes, especially in the topic of tessellation of flat shapes.